2017
DOI: 10.9790/3013-0701012127
|View full text |Cite
|
Sign up to set email alerts
|

A Review On The Diverse Application Of Silver Nanoparticle

Abstract: Abstract:-Nanotechnology is an emerging field with diverse applications in pharmacy, medicine, industries and environments. Among nanosized particles, the inorganic nanoparticles posses unique physical and chemical properties. These nanoparticles and their composites are useful for the wide range of applications. This review aims to provide a consolidated assessment of silver nanoparticle and silver nanocomposites in various fields. Among nanoparticles, silver nanoparticle exhibits antimicrobial activities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The parameter 1/n F has a subunit value (1/n F -0.29), therefore the used adsorbent presents a good affinity for colloidal silver. Considering the heterogeneity factor 1 n s = 0.3, which represents a high deviation from unity, we conclude that the medical bandage adsorbent presents a heterogeneous surface. In addition, from the presented data it can observed that the lowest value of the correlation coefficient was obtained when the experimental data were modeled using Freundlich isotherm.…”
Section: Equilibrium Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…The parameter 1/n F has a subunit value (1/n F -0.29), therefore the used adsorbent presents a good affinity for colloidal silver. Considering the heterogeneity factor 1 n s = 0.3, which represents a high deviation from unity, we conclude that the medical bandage adsorbent presents a heterogeneous surface. In addition, from the presented data it can observed that the lowest value of the correlation coefficient was obtained when the experimental data were modeled using Freundlich isotherm.…”
Section: Equilibrium Studiesmentioning
confidence: 92%
“…Technological development from the last decade lead to extensive usage of colloidal silver in different fields increasing the number of possible applications. Due to the mechanical and physical-chemical properties, colloidal silver is used in several fields: electronics, electrotechniques, biotechnology, bioenergy, textile and optical industries, pharmacy, medicine and environmental protection [1,2]. An extensive literature review proved that colloidal silver has a large number of applications: antibacterial agent [3,4], antifungal agent [5], antiviral agent [6], air disinfection [7], water disinfection [3], ground water biological wastewater treatment [8] and surface disinfection (antimicrobial paints, plastic catheters, gel formulation for specific usage, packing paper for food preservation, clinical clothing) [3].…”
Section: Introductionmentioning
confidence: 99%
“…They are used as thermal conductivity enhancers in various fluid media such as ethylene glycol, water, and oils. They are mainly used because of their stability without forming sedimentation for more prolonged periods [11].…”
Section: The Rationale Behind the Ternary Hybrid Synthesismentioning
confidence: 99%
“…Silver is a non-essential, toxic metal capable of causing damage to biodiversity in aquatic systems worldwide. Growing applications of silver nanoparticles in industrial processes (Thamilselvi and Radha 2017 ) and the resulting increase in contamination of the environment have made silver an increasingly important pollutant to study. The bioavailability and toxicity of silver vary greatly depending on environmental conditions (Paquin and Di Toro 2008 ), life stage (Groh et al 2015 ), and mode of uptake (Hogstrand and Wood 1998 ).…”
Section: Introductionmentioning
confidence: 99%